Mathematical modeling applied to the drying kinetics of black bean starch paste (Research, Society and Development, 2021)
The present study aimed to extract starch from black bean seeds and adjust empirical mathematical models to the data obtained experimentally in its drying kinetics. Starch was extracted from black bean seeds using a sodium metabisulfite solution (0.5%). The paste obtained after the extraction process was subjected to drying kinetics at temperatures of 40, 50 and 60 °C and an air speed of 1.5 m s-1. Empirical mathematical models were adjusted to the experimental data, in which the coefficient of determination (R2) and chi-square function (X2) were evaluated using the statistical indicators and finally the extraction yield was calculated as a percentage of the starch mass obtained in relation to the mass of black beans. The determination coefficient (R2) of all applied models showed values greater than 0.98 (R2> 0.98) and the Page model showed the lowest values for the chi-square function, in which they vary from 0.005637 to 0,003212. The extraction yield values varied from 45.35 to 47.62%, the highest percentage being obtained at a temperature of 60 ° C. However, the Page model at a temperature of 50 °C is the most adequate to represent this study, as it presented the highest value of R2 (0.9998) and the lowest value of the chi-square function (0.3212x10-2).